Benefits of macro-prudential policy in low interest rate environments - Alejandro Van der Ghote (European Central Bank (ECB), 2020)
I study macro-prudential policy intervention in economies with secularly low interest rates. Intervention boosts risk-free real interest rates unintentionally, simply as a by-product of containing systemic risk in financial markets. Thus, intervention also boosts the natural rate of return in particular (i.e., the equilibrium risk-free rate that is consistent with inflation on target and production at full capacity). These results point to a novel complementarity between financial stability and macroeconomic stabilization. Complementary is sufficiently strong to generate a divine coincidence if the natural rate is secularly low, but not too low.
Keywords: E31; E32; E44; 330; Macro-prudential Policy; Systemic Risk; Natural Rate of Return